2021
DOI: 10.1186/s43170-021-00039-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed SSR marker analysis of Diplocarpon coronariae reveals clonality within samples from Middle Europe and genetic distance from Asian and North American isolates

Abstract: Background Apple blotch (AB) caused by Diplocarpon coronariae (Dc) has been established in Europe since 2010. AB is a serious apple disease, mostly in low input orchards and in cider production areas in Northern Italy, Switzerland, Austria and Germany. However, the epidemiology and population genetic structure of this pathogen is unknown. Methods We developed twelve Dc-specific microsatellite markers and screened DNA of both pure fungal isolates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The fact that we could not cause leaf infections from bud, bark or fruit mummy tissues may be due to technical issues, and the role of the various apple tree organs for overwintering of Dc requires further investigation. Dc present on buds and wood in propagation material could be exchanged between nurseries across Europe and may explain the rapid spread of this disease to many European apple production areas since its first detection in Northern Italy (Oberhänsli et al 2021). Our observation that conidia produced on fruits after six months in storage at 4°C are able to infect apple leaves provides an indication that fruit-derived conidia might represent an additional source of primary inoculum at least on a local scale.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The fact that we could not cause leaf infections from bud, bark or fruit mummy tissues may be due to technical issues, and the role of the various apple tree organs for overwintering of Dc requires further investigation. Dc present on buds and wood in propagation material could be exchanged between nurseries across Europe and may explain the rapid spread of this disease to many European apple production areas since its first detection in Northern Italy (Oberhänsli et al 2021). Our observation that conidia produced on fruits after six months in storage at 4°C are able to infect apple leaves provides an indication that fruit-derived conidia might represent an additional source of primary inoculum at least on a local scale.…”
Section: Discussionmentioning
confidence: 74%
“…have not yet been observed in Europe(Wöhner and Emeriewen 2019), indicating it is unlikely they were the spore type captured.Although not yet observed, the importance of ascospores as primary inoculum in Europe should be subject to further research. A recent population genetic study suggested a mixed sexual and asexual reproduction of Dc in Europe, although Dc populations in Europe are genetically homogenous, clonal and dominated by a few multi-locus genotypes(Oberhänsli et al 2021). …”
mentioning
confidence: 99%